STRUKTURALISME GENETIK DALAM NOVEL PUPUK CINTA ORCHIDACEAE KARYA ELIS SRI WIDIANINGSIH - Tania, Ricy; Nadhifah, Salsabila; Hartati, Dian (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to describe human problems in the novel Pupuk Cinta Orchidaceae by Elis Sri Widianingsih. The theory that researchers use is the theory of genetic structuralism from Lucien Goldmann. The research subject is a novel Pupuk Cinta Orchidaceae by Elis Sri Widianingsih. The approach used in this study is a qualitative approach while the research method used is analytic descriptive method. The data collection technique used in this study is the listening technique and the note taking technique. Data analysis techniques, including data reduction, data presentation, and drawing conclusions or verification. The results of the study show that there are human facts, collective subjects, worldviews, the structure of literary works, and the dialectic of understanding explanations as well as the entire parts of the novel Pupuk Cinta Orchidaceae by Elis Sri Widianingsih.